Cultivation Development Vaname Shrimp (Litopenaeus Vannamei) in Randangan District - Erlansyah; Mohamad, Abdurahman Kano; Antu, Yulinda R. (Central Asian Journal of Theoretical and Applied Science, 2022)
This study aims to determine the appropriate policy in the use of pond land for vaname shrimp (Litopenaeus vannamei) cultivation. The method used in this research is using Process Hierarchy Analysis (AHP). The results showed that the sequence of strategic plans for the development of vaname shrimp (Litopenaeus vannamei) in Randangan District was the availability of human resources with a value of (0.489), venture capital loans (0.235), infrastructure (0.111), market demand (0.094), and suitability of cultivated land (0.071).